The three Rs: Academic Language and Learning (ALL) Advisers getting down to basics with academic colleagues - Briguglio, Carmela (Association for Academic Language and Learning, 2007)
As academic advisers, how we communicate our role and work to academic colleagues affects if and how they will use the services we provide and how they view us. It also influences how they perceive the value of our work andwhether they in fact consider us colleagues in the process of tertiary teaching and learning, or merely adjuncts and “outsiders”. This paper argues that in order for our work to flourish and be highly regarded we need to promote the three Rs: Resources, Room and Respect. The first of these, Resources, is easy to understand – unless we are provided with sufficient well qualified staff and the necessary material resources, it is difficult to provide anexcellent service. The second, Room to move, indicates that staff need to be allowed enough room to experiment and grow in their role. The third, Respect for our work, we should both expect and earn through providing an excellent, well-informed and effective service which makes a difference to the quality of the teaching and learning experience of both students and staff. This paper examines the way we pitch our message when we “sell” our services and discusses whether we in fact address the above three Rs when communicating with academic colleagues.